The role of structural and functional parameters in designing pathology-specific tDCS protocols for primary progressive aphasia - Sagarika Bhattacharjee; P. T. Sivakumar; Ganesan Venkatasubramanian; Kenichi Oishi; Kyrana Tsapkini; S. H. Annabel Chen; Brenda Rapp; John E. Desmond; T. N. Sathyaprabha; Kaviraja Udupa; Rajan Kashyap (Alzheimer’s Research & Therapy)
Abstract Background The two subtypes of primary progressive aphasia (PPA) associated with Frontotemporal Lobar Degeneration (FTLD)—non-fluent (nfvPPA) and semantic (svPPA)—have distinct structural and functional abnormalities. Transcranial direct current stimulation (tDCS) targets the language network to address deficits, yet a single, arbitrary montage is often applied despite pathophysiological differences. Since tDCS current distribution depends on brain structure and function, variant-specific montages are essential. This study presents a pathology-specific approach for tDCS montage selection, identifying the optimal montage for each PPA variant. Method T1-weighted and resting-state fMRI data from 38 healthy, 31 nfvPPA and 32 svPPA subjects were obtained. Grey matter volume and functional entropy were analysed across 116 brain regions. Patients and controls were compared to identify significant differences in atrophy and entropy. Electric-field modelling of three widely used dorsal, ventral, and frontal tDCS montages provided current intensity estimates in the language network. Canonical Correlation Analysis examined the relationship between current intensity, atrophy, and entropy. Results Structural and functional changes differed between the two PPA variants: nfvPPA showed left frontal atrophy and reduced entropy in the left parietal/cerebellar areas, while svPPA exhibited left temporal atrophy and reduced entropy in the left frontal and right temporal regions. Atrophy distribution primarily influenced tDCS current spread, determining montage suitability. In nfvPPA, the frontal montage showed a strong association between delivered current and grey mettwr volume of atrophied areas, whereas in svPPA, a similar pattern was observed for the ventral montage. Conclusion The study identifies the frontal montage as the most suitable for nfvPPA and the ventral montage for svPPA. This study highlights the importance of pathology-specific tDCS montage selection, emphasizing the need for variant-based modulation of the language network in PPA.